The Semantic Deviations of The Dyak Chief Poem by Erwin Clarkson Garrett - Tiya Ilahi, Putera; Arifin, Muhammad Bahri; Sanhadi Rahayu, Famala Eka (Fakultas Ilmu Budaya Universitas Mulawarman, 2023)
Poetry is a literary genre that evolved throughout times, but features a common identity: deviations from linguistics norm to attain aesthetic value. One of such poems is Erwin Clarkson Garrett’s The Dyak Chief. This research aims to identify and analyze the semantic deviations featured in the The Dyak Chief and how the deviants related to the narrative quality of the poem. The objective of this research is to answer two research questions that the researcher addressed: the types of semantic deviations and how they serve the meaning purpose of the poem. The present research is a qualitative study with stylistics approach. Furthermore, the concept of narrative poetry was also elaborated in order to answer on how the deviants serve the meaning of the poem. Based on the conducted research, the poem contains the three main tropes of semantic deviation: semantic oddity (except for paradox), transference of meaning, and honest deceptions (except for litotes). Moreover, these deviations provided revelation, emotional aspect of the main character, and themes of The Dyak Chief. This deviants in turn helped to built the feature of the poem in regards of these three aspects as a narrative poetry.Keywords: stylistics, semantic deviations, The Dyak Chief, poetry, narrative